UPAYA APARATUR KEPALA DESA DALAM MENINGKATKAN LAYANAN PUBLIK DI DESA PADANGSAMBIAN KAJA KECAMATAN DENPASAR BARAT KOTA DENPASAR - SUDIARTA, I NENGAH (Widya Accarya, 2018)
ABSTRACT Success or failure in the implementation of community services is influenced by leadership and supported by adequate government, then the implementation of good governance (good governance) will be realized. The main task of the Village Head's government is to exercise some of the sub-district authorities and to carry out other tasks based on the prevailing regulations. In its capacity as a government organization under the sub-district, the objective of governing the Village Head is the implementation of various functions of the Village Head in accordance with the authority given by the kecamatan effectively and efficiently, including the function of administrative services of the apparatus to the community.The problem revealed in this research is how the efforts of the Village Head's apparatus in improving the public service? The objective of this research is to know the role of government apparatus of Padangsambian Kajadalam Village Head to improve the implementation of public service. In this research, the writer uses the theoretical base based on the research title, that is the Effort Effort of the Village Head In Improving the Public ServiceFrom the research, the result shows that there are efforts of apparatus of Padangsambian Kaja Village Head of West Denpasar which is very influential in the effort to provide excellent service for the community of Padangsambian Kaja Village Head of West Denpasar and the society from outside who need the service. This can be seen from the environment and the life of the people of Padangsambian Kaja West Denpasar who is clean, peaceful, peaceful, prosperous, and not found many complaints or criticism from the public about the implementation of public service conducted by apparatus Padangsambian Kaja Village Head West Denpasar in the suggestion box provided. Keywords: Attempt apparatus, Village Head of Padangsambian Kaja, public            service.